Enhancing Students’ Writing Skill of Short Story through Mind Mapping in MTs Muhammadiyah 13 Solokuro - Fais Wahidatul Arifatin (Jurnal Siliwangi: Seri Pendidikan, 2021)
This study is kind of classroom action research that focused on how to enhance the students’ writing skill. To enhance the students’ skill in writing, the writer used mind mapping technique. The difficulties in writing for the beginner is how to organize the idea become a pragraph that can be coherence one another. The object of the study is the students of 9th grade in MTs Muhammadiyah 13 Solokuro Lamongan in time periode 2021/2022. The students of junior high school got difficulties in writing in their age, that is why mind mapping technique is really needed to motivate and enhance the students in writing skill. The pre-test and post-test are given in this study to know the improvement of their writing skill. The writing skill for the students in this case is focusing in writing a short story or it can be known as writing a narrative text. The results of this study shown that there is improvement in ellaborating the idea through mind mapping and it can enhance the students wtiring skill.